2019
DOI: 10.1016/j.jnt.2018.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Noncongruence subgroups and Maass waveforms

Abstract: The main topic of the paper is spectral theory for noncongruence subgroups of the modular group. We have studied a selection of the main conjectures in the area: the Roelcke-Selberg and Phillips-Sarnak conjectures and Selberg's conjecture on exceptional eigenvalues. The first two concern the existence and nonexistence of an infinite discrete spectrum for certain types of Fuchsian groups and last states that there are no exceptional eigenvalues for congruence subgroups, or in other words, there is a specific sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(43 citation statements)
references
References 55 publications
4
39
0
Order By: Relevance
“…(2.37) Doran showed that there are 33 modular RES [87], which can be extended to 47 distinct RES, as we will see in the next subsection. Our approach is different from that of [87] and closer to the construction of Shioda [27]; we will use the classification of subgroups of PSL(2, Z) [88][89][90] and the map (2.37) in order to find all modular rational elliptic surfaces. This will be done explicitly in section 4.…”
Section: Modular Elliptic Surfacesmentioning
confidence: 99%
See 3 more Smart Citations
“…(2.37) Doran showed that there are 33 modular RES [87], which can be extended to 47 distinct RES, as we will see in the next subsection. Our approach is different from that of [87] and closer to the construction of Shioda [27]; we will use the classification of subgroups of PSL(2, Z) [88][89][90] and the map (2.37) in order to find all modular rational elliptic surfaces. This will be done explicitly in section 4.…”
Section: Modular Elliptic Surfacesmentioning
confidence: 99%
“…As shown in [87], this is a set of 33 surfaces, up to quadratic twists, which then extends to 47 different surfaces in Persson's classification [3,4]. The subgroups of PSL(2, Z) associated to each modular rational elliptic surface can be deduced from the list of genus 0 subgroups of PSL(2, Z) of index less or equal to 12 [88][89][90], together with the map (2.37).…”
Section: Modular Coulomb Branchesmentioning
confidence: 99%
See 2 more Smart Citations
“…Versions of the Weyl law with error estimates are available in the constant curvature case, see e.g. [34]. 7 Examples and numerical studies 7.1 General set-up In this section we will consider several examples of manifolds with cusps.…”
Section: Embedded Eigenvaluesmentioning
confidence: 99%